Indonesian Spelling Mastery and Student Writing Result - Erdlanda, Febry Marindra Cysbya (Journal of Education, Language Innovation, and Applied Linguistics, 2025)
This study discusses the students’ mastery of Indonesian spelling, the description of the use of spelling in students’ writing results, and the correlation between the two. The research method is a descriptive method used to systematically and accurately explain facts about an object under study on these three topics. The test is used as a data collection technique that is needed with the test sheet instrument in the form of objective tests and subjective tests tested on students. The results showed that: (1) Based on the average value of a sample of 41 students, 28 students, or more than half (68%) were sufficient to master standard Indonesian spelling, while the remaining 13 students or less than half (32%) were less mastering standard Indonesian spelling; (2) A total of 21 (twenty-one) students or more than half (51%) were stated to have good writing results based on spelling aspects, while the remaining 20 (twenty) students or less than half (49%) were stated to have written results not good seen based on the spelling aspect; and (3) Obtained r count price = -0.050 while r price of product-moment table for a significant level of 5% = 0.308 and significant level of 1% = 0.396 at n = 41. Based on the calculation, results show the price of r count (-0.050) is smaller than the price of r table, both for a significant level of 5% (-0.050 0.308) and for a significant level of 1% (-0.050 0.396). It can be concluded that there is no correlation or relationship. Keywords: Correlation; Indonesian spelling; writing results.